STUDY OF PREVALENCE OF THE INFANT-JUVENILE OBESITY IN SCHOLARS (Fiep Bulletin - online, 2014)
The obesity became a growing world epidemic, presenting a larger risk if initiated in the childhood and adolescence. This study evaluated the prevalence of obesity in scholars of Conselheiro Lafaiete city and related factors. It was measured 112 students (52 boys and 60 girls) with age varying between 11 and 17 years old from Queluz de Minas School.  It was measured the body weight and the height for determination of the Body Mass Index (BMI). The appraised answered a questionnaire on habitual levels of physical activity (NAF). The overweight and obesity classification was adopted the recommendation of World Health Organization (WHO, 1995). The prevalence of overweight and obesity was similar for both sexes (approximately 15%). According the results obtained by NAF, it was observed a larger prevalence of eutrophycs moderately active or very active in relation to overweight and obese (p
Keywords: obesity; physical activity; children; adolescences